2019
DOI: 10.3390/jcdd6040035
|View full text |Cite
|
Sign up to set email alerts
|

The Non-Fibrillar Side of Fibrosis: Contribution of the Basement Membrane, Proteoglycans, and Glycoproteins to Myocardial Fibrosis

Abstract: The extracellular matrix (ECM) provides structural support and a microenvironmentfor soluble extracellular molecules. ECM is comprised of numerous proteins which can be broadly classified as fibrillar (collagen types I and III) and non-fibrillar (basement membrane, proteoglycans, and glycoproteins). The basement membrane provides an interface between the cardiomyocytes and the fibrillar ECM, while proteoglycans sequester soluble growth factors and cytokines. Myocardial fibrosis was originally only linked to ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 183 publications
1
20
0
1
Order By: Relevance
“…The ECM constitutes a complex network of fibrillary (fibrillar collagens) and non-fibrillary (composed by the basement membrane, proteoglycans, and glycoproteins) components within the extracellular space that have both signaling and structural functions ( Chute et al, 2019 ). New proteomic approaches have revealed that 90% of cardiac ECM is composed of 10 different proteins, from which serum albumin, collagens (collagens I, III, and IV), non-collagenous glycoproteins [fibronectin (FN) and laminin], proteoglycans, glucosaminoglycans (GAGs), and elastins are the most common ( Lindsey et al, 2018 ).…”
Section: Cardiac Ecmmentioning
confidence: 99%
“…The ECM constitutes a complex network of fibrillary (fibrillar collagens) and non-fibrillary (composed by the basement membrane, proteoglycans, and glycoproteins) components within the extracellular space that have both signaling and structural functions ( Chute et al, 2019 ). New proteomic approaches have revealed that 90% of cardiac ECM is composed of 10 different proteins, from which serum albumin, collagens (collagens I, III, and IV), non-collagenous glycoproteins [fibronectin (FN) and laminin], proteoglycans, glucosaminoglycans (GAGs), and elastins are the most common ( Lindsey et al, 2018 ).…”
Section: Cardiac Ecmmentioning
confidence: 99%
“…Our study provides information about the role of the non-fibrillar proteins in myocardial fibrosis. The extracellular proteoglycans such as aggrecan, the small leucine-rich proteoglycans, including decorin and lumican, and the cell surface proteoglycan syndecan-4 [ 10 , 30 ] were the principal proteoglycans altered in cardiac fibrosis associated with mitral valve fibromyxomatous degeneration that could lead to MVP. The extracellular proteoglycans are the main proteoglycans involved in the stabilization of the ECM and collagen synthesis [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The extracellular proteoglycans such as aggrecan, the small leucine-rich proteoglycans, including decorin and lumican, and the cell surface proteoglycan syndecan-4 [ 10 , 30 ] were the principal proteoglycans altered in cardiac fibrosis associated with mitral valve fibromyxomatous degeneration that could lead to MVP. The extracellular proteoglycans are the main proteoglycans involved in the stabilization of the ECM and collagen synthesis [ 10 ]. Decorin and lumican are increased in myocardial fibrosis following pressure overload or myocardial infarction [ 31 ], while syndecan-4 contributes to myofibroblast differentiation in these settings [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MI is touted as the most common cause of human death worldwide correlated with partial or complete occlusion of microvasculature in the affected areas [8]. In most MI patients, the lack of sufficient blood supplementation to the infarcted area leads to extensive necrosis and aberrant ECM remodeling [9]. Restorative compensatory mechanisms and promotion of fibroblasts in MI patients contribute to the bulk secretion of type I collagen in the interstitial spaces, leading to insufficient myocardial tissue and diastolic dysfunction [10].…”
Section: Introductionmentioning
confidence: 99%